THE DIATOPICAL HERMENEUTICS: R. PANIKKAR’S RESPONSE TO THE SCIENTIFIC STUDY OF RELIGIONS - Raj , L Anthony Savari (Journal of Dharma, 1996)
Raimon Panikkar is one of today’s leading scholars of Comparative Philosophy and Religious Studies. Attention will be focussed in this paper to spell out his response to the contemporary scientific study of religions. This response, to be sure, is marked by his Diatopical Hermeneutics with the Dialogical Dialogue as the proper method.